2014
DOI: 10.1016/j.virol.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of genome-attached bacteriophage terminal proteins

Abstract: Protein-primed replication constitutes a generalized mechanism to initiate DNA or RNA synthesis in linear genomes, including viruses, gram-positive bacteria, linear plasmids and mobile elements. By this mechanism a specific amino acid primes replication and becomes covalently linked to the genome ends. Despite the fact that TPs lack sequence homology, they share a similar structural arrangement, with the priming residue in the C-terminal half of the protein and an accumulation of positively charged residues at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…Such genes are generally located near the polymerase gene but very poorly conserved. Terminal proteins share features like a small size and a high isoelectric point [72,73]. Based on these criteria, IDF_05 appears the best candidate (Table S4) but additional investigations are needed to confirm this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Such genes are generally located near the polymerase gene but very poorly conserved. Terminal proteins share features like a small size and a high isoelectric point [72,73]. Based on these criteria, IDF_05 appears the best candidate (Table S4) but additional investigations are needed to confirm this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…The proteins responsible for this are covalently linked to the phage genome ends and contain eukaryotic nuclear localization signals that promote their accumulation in the nucleus. Once inside the eukaryotic cell, these terminal proteins provide mechanism for localizing foreign DNA for gene expression or even integration into the cell genome 17 , 63 . Our pulse-chase experiment showed that the internalized phages could be recovered from the cells in their infective form up to 24 h, followed by an effective inactivation of phages within the cells.…”
Section: Discussionmentioning
confidence: 99%
“…This study reports a survey of phages of AAB collected from grapes which resulted in the isolation and sequencing of a novel phage infecting G. cerinus , representing a novel member of the family Tectiviridae . Tectiviruses have tailless virions consisting of an icosahedrally organized proteinaceous capsid that surrounds a protein-rich lipid membrane, enclosing a linear double-stranded (ds) DNA genome with inverted terminal repeats and covalently attached terminal proteins [ 18 , 19 , 20 , 21 , 22 ]. Currently known tectiviruses are classified into two genera, Alphatectivirus and Betatectivirus [ 23 ].…”
Section: Introductionmentioning
confidence: 99%